Basic polymer engineering data - Rao, Natti S. (Hanser Publications, 2017)
Shows how to apply basic design data to solve practical problems in polymer engineering, via numerous examples. The book offers both resin and up-to-date machine design data, and shows how resin-compatible polymer processing equipment can be designed by using computational procedures based on thermodynamics and rheology.
Keywords: Polymers.; elektronické knihy; electronic books